Strategi Integrasi Pendidikan Nilai Budaya Lokal Sandur Manduro di Dusun Gesing, Kabupaten Jombang Jawa Timur - Robby Hidajat; Ponimin Ponimin; Wida Rahayuningtyas; Muhammad Sirojul Muniir (Universitas Medan Area, 2025)
This article describes a strategy for preserving local cultural values through the Sandur Manduro performing art in Gesing Hamlet, Manduro Village, Jombang, East Java. The research subject is the Sandur Panji Arum association, led by Rifain, which consistently strives to preserve and develop this traditional performing art. The study aims to recommend the integration of Sandur Manduro into both formal and informal art education as a sustainable effort to maintain local cultural values. Sandur Manduro holds significant potential as an effective dance art education material to strengthen the identity and local cultural values among students in Jombang. Using a qualitative case study approach, this research analyzes the strategies employed by the Sandur Panji Arum association in transmitting knowledge and practices of Sandur performing art to the community, especially school-aged children and adolescents. Data were collected through participant observation, in-depth interviews with Rifa'in and association members, and analysis of related documents. The findings indicate the active role of the Sandur Manduro performing art's revitalization in instilling noble values, including togetherness, cooperation, and local wisdom, embedded within Sandur Manduro performances.